Coordination of the Arc Regulatory System and Pheromone-Mediated Positive Feedback in Controlling the Vibrio fischeri lux Operon - Septer, Alecia N.; Stabb, Eric V. (PLOS ONE, 2012)
Bacterial pheromone signaling is often governed both by environmentally responsive regulators and by positive feedback. This regulatory combination has the potential to coordinate a group response among distinct subpopulations that perceive key environmental stimuli differently. We have explored the interplay between an environmentally responsive regulator and pheromone-mediated positive feedback in intercellular signaling by Vibrio fischeri ES114, a bioluminescent bacterium that colonizes the squid Euprymna scolopes. Bioluminescence in ES114 is controlled in part by N-(3-oxohexanoyl)-L-homoserine lactone (3OC6), a pheromone produced by LuxI that together with LuxR activates transcription of the luxICDABEG operon, initiating a positive feedback loop and inducing luminescence. The lux operon is also regulated by environmentally responsive regulators, including the redox-responsive ArcA/ArcB system, which directly represses lux in culture. Here we show that inactivating arcA leads to increased 3OC6 accumulation to initiate positive feedback. In the absence of positive feedback, arcA-mediated control of luminescence was only ∼2-fold, but luxI-dependent positive feedback contributed more than 100 fold to the net induction of luminescence in the arcA mutant. Consistent with this overriding importance of positive feedback, 3OC6 produced by the arcA mutant induced luminescence in nearby wild-type cells, overcoming their ArcA repression of lux. Similarly, we found that artificially inducing ArcA could effectively repress luminescence before, but not after, positive feedback was initiated. Finally, we show that 3OC6 produced by a subpopulation of symbiotic cells can induce luminescence in other cells co-colonizing the host. Our results suggest that even transient loss of ArcA-mediated regulation in a sub-population of cells can induce luminescence in a wider community. Moreover, they indicate that 3OC6 can communicate information about both cell density and the state of ArcA/ArcB.